Case report: Metastatic pancreatic neuroendocrine tumour associated with portal vein thrombosis; successful management with subsequent pregnancies - Sira, Lívia; Zsíros, Noémi; Bidiga, László; Barna, Sándor; Kanyári, Zsolt; Nagy, Edit B.; Guillaume, Nicolas; Wild, Damian; Rázsó, Katalin; Andó, Szilvia; Balogh, István; Nagy, Endre V.; et al. (Frontiers in Endocrinology, 2023)
Background Splanchnic vein thrombosis due to co-existing metastatic pancreatic neuroendocrine tumour (pNET) and JAK2V617F mutation is a rare condition. Case report Here we present a case of a young woman with complete remission of a non-functioning grade 2 pNET with unresectable liver metastases, coexisting with JAK2V617F mutation. Splenectomy and distal pancreatectomy were performed. Neither surgical removal, nor radiofrequency ablation of the liver metastases was possible. Therefore, somatostatin analogue (SSA) and enoxaparine were started. Peptide receptor radionuclide therapy (PRRT) was given in 3 cycles 6-8 weeks apart. Genetic testing revealed no multiple endocrine neoplasia type 1 (MEN-1) gene mutations. After shared decision making with the patient, she gave birth to two healthy children, currently 2 and 4 years old. On pregnancy confirmation, SSA treatment was interrupted and resumed after each delivery. Ten years after the diagnosis of pNET, no tumour is detectable by MRI or somatostatin receptor scintigraphy. PPRT, followed by continuous SSA therapy, interrupted only during pregnancies, resulted in complete remission and enabled the patient to complete two successful pregnancies.